2015
DOI: 10.1177/0032885515596509
|View full text |Cite
|
Sign up to set email alerts
|

To Learn or Not to Learn—This Is the Question

Abstract: This research explores the rate of learning disabilities (LD) within the Hebrewspeaking adult prison population in Israel, examining the relationship between LD and dropping out of school with criminal behavior. The study finds that the frequency of LD is very high among Israeli inmates (69.6%) and that a gap exists between LD inmates' awareness of their scholastic weakness in school and the educational system's ignorance. Implications of these results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the present study school dropout was examined from a multidimensional approach, where individual, family and school (Andrei et al, 2012; Bjerk, 2012; Fortin et al, 2013; Korhonen et al, 2014) correlates of school dropout were analyzed among juvenile offenders, a population with a high risk of school dropout (Lochner and Moretti, 2004; Dianda, 2008; Ou and Reinolds, 2010; Andrei et al, 2012; De Witte et al, 2013; Korhonen et al, 2014; Einat and Einat, 2015; Lucero et al, 2015; Herrero et al, 2016; Jaggers et al, 2016). The official records of 264 juvenile delinquents were used to analyze the individual, family, and school correlates of school dropout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study school dropout was examined from a multidimensional approach, where individual, family and school (Andrei et al, 2012; Bjerk, 2012; Fortin et al, 2013; Korhonen et al, 2014) correlates of school dropout were analyzed among juvenile offenders, a population with a high risk of school dropout (Lochner and Moretti, 2004; Dianda, 2008; Ou and Reinolds, 2010; Andrei et al, 2012; De Witte et al, 2013; Korhonen et al, 2014; Einat and Einat, 2015; Lucero et al, 2015; Herrero et al, 2016; Jaggers et al, 2016). The official records of 264 juvenile delinquents were used to analyze the individual, family, and school correlates of school dropout.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has traditionally analyzed dropout and delinquency in adult samples, mostly penitentiary samples, where crime has been studied as a result of school dropout and other school factors, such as school belonging (Lucero et al, 2015), learning-disabilities, attitudes toward school and scholastic experiences (Einat and Einat, 2015), school expulsion (Jaggers et al, 2016) or school mobility (Ou and Reinolds, 2010). For instance, Dianda (2008) found that 41% of inmates in state and federal prisons in the United States had less than a high school education, indicating that inmates who were dropouts were more likely to have served a prior sentence in prison and were more likely to have been sentenced when they were young.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation